Polar and extrahilar renal arteries: A case report - Tivcheva, Yoanna Vladimirova; Angelov, Mihail; Krastev, Nikolai; Kirilov, Cvetomir; Krastev, Dimo; Jelev, L; Apostolov, A (Archives of Community Medicine and Public Health, 2023)
Introduction: The vascular system has a high frequency of variations, which are of interest to both anatomists and clinicians, as well as surgeons. The renal vasculature is quite variable and given the significant number of variations, the latter has proven difficult to classify. The conflicting terminology is often the cause of a poor understanding of the clinical implications of the presence of such variations. We present a case of bilateral accessory arteries, which can be classified as polar and extrahilar. Background: Variants of the renal artery are a common finding with additional vessels in up to 30% of cases. The supernumerary arteries are of end type and often enter the kidney outside the hilum. The arteries that enter the kidney in its upper or lower pole are referred to as polar arteries. Case report: During a routine dissection of a 73-year-old, female, formalin-fixed cadaver at the department of Anatomy, Histology and Embryology at the Medical University of Sofia, we discovered a right inferior polar artery and a left extrahilar renal artery, both originating from the abdominal aorta. The right kidney was located at the level of L1- L2. Conclusion: Accessory renal vessels have been an object of multiple cadaveric and in vivo studies. The terminology and classification of such variations in regard to their origin, course, and site of entrance in the kidney are conflicting and often prove inadequate to convey the clinical and surgical importance of their presence. Knowledge of such variants is of great significance when performing an explorative laparotomy, kidney transplantation, and assessing kidney injury. Such vessels are as well associated with cases of hypertension, hydronephrosis and other conditions.